Synthesis of promising copper nanoparticles utilizing biocontrol agents, Trichoderma virens and Chaetomium globosum - DORJEE, LHAM; KAMIL, DEEBA; KUMAR, RAJESH; KHOKHAR, M K; AGGARWAL, RASHMI; GOGOI, ROBIN (The Indian Journal of Agricultural Sciences, 2024)
The pursuit of creating safe and efficient pesticides remains an ongoing aspiration. Recently, the potential efficacy of metal nanoparticles against diverse phytopathogens has come to light. Commonly used methods, viz. chemical and physical means of nanoparticle synthesis are associated with a range of drawbacks. Fortunately, the biological synthesis method ensures safe and non-toxic nanoparticles. The present study was carried out during 2022–23 at ICAR- Indian Agricultural Research Institute, New Delhi, which documented the successful synthesis of copper nanoparticles (CuNPs) utilizing the supernatant of potent fungal biocontrol agents, viz. Trichoderma virens and Chaetomium globosum. The reduction in the size of copper was determined by UV-Vis spectroscopy. The change in colour of the reaction mixture confirmed the reduction in the size of particles. Characterization using TEM measured spherical CuNPs of the size range 8 to 100 nm depending on the CuSO4 concentration used. Furthermore, Fourier Transform Infrared Spectroscopy (FTIR) unveiled the presence of several functional groups that plays pivotal role in reducing and stabilizing particle size. The in vitro assay conclusively demonstrated the effectiveness of biosynthesized CuNPs, with significant inhibition at a concentration of 10 µg/ml in the case of Xanthomonas euvesicatoria and at 50 µg/ml in the case of Enterobacter cloacae. Our study marks the first instance of synthesizing CuNPs through the utilization of two aforesaid fungal species holding significant promise for antibacterial applications.